Metabolic response of prostate cancer to nicotinamide phophoribosyltransferase inhibition in a hyperpolarized MR/PET compatible bioreactor. Issue 14 (14th July 2015) - Keshari, Kayvan R.; Wilson, David M.; Van Criekinge, Mark; Sriram, Renuka; Koelsch, Bertram L.; Wang, Zhen J.; VanBrocklin, Henry F.; Peehl, Donna M.; O'Brien, Tom; Sampath, Deepak; Carano, Richard A. D.; Kurhanewicz, John
<x xml:space="preserve">Abstract</x> BACKGROUND Metabolic shifts in disease are of great interest for the development of novel therapeutics. In cancer treatment, these therapies exploit the metabolic phenotype associated with oncogenesis and cancer progression. One recent strategy involves the depletion of the cofactors needed to maintain the high rate of glycolysis seen with the Warburg effect. Specifically, blocking nicotinamide adenine dinucleotide (NAD) biosynthesis via nicotinamide phosphoribosyltransferase (NAMPT) inhibition depletes cancer cells of the NAD needed for glycolysis. To characterize this metabolic phenotype in vivo and describe changes in flux with treatment, non‐invasive biomarkers are necessary. One such biomarker is hyperpolarized (HP) [1‐13C] pyruvate, a clinically translatable probe that allows real‐time assessment of metabolism. METHODS We therefore developed a cell perfusion system compatible with HP magnetic resonance (MR) and positron emission tomography (PET) to develop translatable biomarkers of response to NAMPT inhibition in reduced volume cell cultures. RESULTS Using this platform, we observed a reduction in pyruvate flux through lactate dehydrogenase with NAMPT inhibition in prostate cancer cells, and showed that both HP lactate and 2‐[18F] fluoro‐2‐deoxy‐D‐glucose (FDG) can be used as biomarkers for treatment response of such targeted agents. Moreover, we observed dynamic flux changes whereby HP pyruvate was re‐routed to alanine, providing both positive and negative indicators of treatment response. CONCLUSIONS This study demonstrated the feasibility of a MR/PET compatible bioreactor approach to efficiently explore cell and tissue metabolism, the understanding of which is critical for developing clinically translatable biomarkers of disease states and responses to therapeutics. Prostate 75:1601–1609, 2015. © 2015 Wiley Periodicals, Inc.